Psychological dispositions in the face of disasters among psychology students at two private universities - Valero Álamo, Santiago (2015)
The article presents the results of an investigation was conducted with psychology students at private universities “Ricardo Palma” in Lima and “Alas Peruanas” filial Ica, in order to describe and compare psychological dispositions disaster situations, they used the method based on the application of cross-sectional surveys using the “Scale of psychological provisions to different types of states of emergency confronts natural and social origin” DPEENS- 1998, designed and validated by the Ps. Luis Vicuña.The research was applicative given that the results can be applied or used immediately for designing training plans, motivation and preparedness for emergencies and / or disasters; the sample consisted of 150 students of the Private University “Ricardo Palma” - Lima and 118 of the Private University “Alas Peruanas” filial Ica, giving a total population of 276 psychology students.The research results show us that there are significant differences between students of psychology at the Private University “Ricardo Palma” of Lima and the Private University “Alas Peruanas” filial - Ica, what concerning the conduct expected to finalize a disaster, in terms of the perception towards natural disasters with the passage of time, the attitudes towards disaster drills and foreign aid, the perception of the management of aid during natural disasters and reaction to join a brigade of Civil Defense.